2013
DOI: 10.1080/19338244.2013.807762
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Musculoskeletal Disorders Among Korean Police Personnel

Abstract: This study was conducted to investigate efficient, systematic management of the Korean police and to examine the status and prevention of musculoskeletal disorders in Korean police officers. For police officers in special working environments, the importance of basic data is emphasized for human resources (HR) management and the prevention of industrial hazards from an industrial health care perspective. This study was conducted on police officers who visited the national police hospital and who underwent x-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The lower back was the body part with the highest prevalence of pain among police officers. In agreement with our findings, previous studies have also observed a high prevalence of pain in the lower back region followed by the neck and dorsal region among military soldiers (18) and police personnel (15) . The lower back is a common site of MSD symptoms, a condition that can lead to a high level of disability (19) .…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…The lower back was the body part with the highest prevalence of pain among police officers. In agreement with our findings, previous studies have also observed a high prevalence of pain in the lower back region followed by the neck and dorsal region among military soldiers (18) and police personnel (15) . The lower back is a common site of MSD symptoms, a condition that can lead to a high level of disability (19) .…”
Section: Methodssupporting
confidence: 83%
“…However, more than half of the police officers reported an acute problem over the last seven days. MSD symptoms may be associated with the natural aging process, or it may be triggered by job overloading, exposure to vibration, inadequate working conditions, ergonomic factors, muscle overload, awkward postures, physical inactivity, and overweight (14)(15)(16) . Another important point is the use of a bulletproof vest and personal protective equipment, which may be associated with some MSD symptoms when worn on a daily basis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following removal of duplicates, all identified studies were then screened by title and abstract using pre-defined inclusion and exclusion criteria. Injury definitions varied across 5 of the included studies [6,11,12,13,14]. In the remaining studies injury was not defined.…”
Section: Methodsmentioning
confidence: 99%
“…Considering this, for the purpose of this review, all studies which investigated law enforcement officers who were considered to have sustained ‘an injury’ were included. Several studies [7,13,14,15,16,17] did not specify whether the reported injuries occurred while the officer was on duty, whereas the remaining studies only included injuries that occurred whilst an officer was on duty [5,6,11,12,15,18,19,20,21,22]. The full criteria are detailed in Table 2.…”
Section: Methodsmentioning
confidence: 99%